Not Just Rain: Quantitative Evidence of the Impact of Historical Rainfall Period 2016-2021 on Palm Oil Production in Riau Indonesia - Gunawan, Sri; Pratama, Oktarianto Tidar; Nurcahyono, Nurcahyono (Akademi Komunitas Perkebunan Yogyakarta, 2025)
Environmental factors greatly influence oil palm productivity, especially rainfall, which impacts the plant's physiological state. This study aims to analyze the relationship between rainfall and oil palm production. This study used a two-stage survey method. Time series data from 2016-2021 were used to evaluate the relationship between monthly rainfall and three production parameters (productivity, number of fresh fruit bunches (FFB), and average bunch weight (ABW). Correlation and regression analyses were conducted to identify significant contributions of rainfall to yield variables by considering the time lag. The results showed that rainfall that occurred 24-36 months previously had a significant effect on productivity and the number of FFB with R2 values of 53.93% and 54.83%, and rainfall 37-38 months previously contributed to BJR with an R2 value of 40.33%. Rainfall has historically played an important role in determining oil palm yields. Plantation management based on long-term climatological data can be a new approach to optimizing sustainable oil palm production.